Search for massive resonances decaying into WW, WZ or ZZ bosons in proton-proton collisions at √s=13 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Asilar, Ece; Bergauer, Thomas; Md. Ali, Mohd. Adli (Springer Verlag, 2017)
A search is presented for new massive resonances decaying to WW, WZ or ZZ bosons in `νqq¯ and qqq¯ q¯ final states. Results are based on data corresponding to an integrated luminosity of 2.3–2.7 fb−1 recorded in proton-proton collisions at √ s = 13 TeV with the CMS detector at the LHC. Decays of spin-1 and spin-2 resonances into two vector bosons are sought in the mass range 0.6–4.0 TeV. No significant excess over the standard model background is observed. Combining the results of the `νqq¯ and qqq¯ q¯final states, cross section and mass exclusion limits are set for models that predict heavy spin-1 and spin-2 resonances. This is the first search for a narrow-width spin-2 resonance at √ s = 13 TeV.